Free Vibration and Bending of Gradient Auxetic Plate Using Finite Element Method - Cong, Pham Hong; Tung, Vu Dinh; Hai, Do Duc; Khoa, Nguyen Dinh (VNU Journal of Science: Mathematics - Physics, 2021)
In recent years, there has been a new approach to the material industry that uses sandwich structures with auxetic honeycomb cores with the interesting property of negative Poisson's ratios. In this paper, the Finite Element Method (in ANSYS) is used to investigate natural frequency of vibration and bending characteristics under varying pressure loads applied on the top skin when changing fundamental properties of some gradient configurations, including angular gradient, thickness gradient and functional gradient configurations of the auxetic plate with honeycomb structure. Thereby, the advantages of each configuration are investigated, studied, and obtained; therefore, it is expected to be applied in various industry sectors, such as wind turbine blades, aircraft wings, among others.